Development of Photovoltaic Devices Based on Near Infrared Quantum Dots and Conjugated Polymers. Issue 7 (30th May 2016) - Tan, Long; Li, Pandeng; Sun, Baoquan; Chaker, Mohamed; Ma, Dongling
Abstract: For decades, solution‐processable, light absorbing semiconductor materials of quantum dots (QDs) and conjugated polymers have been extensively studied in third‐generation photovoltaic (PV) devices, targeting both high efficiency and low cost, due to their various advantages. It is promising to fabricate PV devices by further combining near infrared (NIR) QDs and conjugated polymers, which can potentially merge the respective advantages of both polymers and inorganic nanomaterials in mechanical flexibility, specific weight, light absorption and photostability. In this review article, we first present the application of NIR QDs in organic solar cells built upon traditional polymers. Exciton dissociation and charge carrier transport are described, and strategies for improving the performance of these devices are analyzed. Then, the developments of NIR QDs‐polymer hybrid solar cells based on recently developed low‐bandgap polymers are summarized. Finally, future perspectives are discussed. Abstract : Rational combination of near infrared quantum dots (NIR QDs) and conjugated polymers into inorganic–organic hybrid photovoltaic devices can in principle merge the respective advantages of polymers and inorganic nanomaterials in light absorption, mechanical flexibility, specific weight, and photostability. This provides ample area for developing high‐efficiency NIR QDs‐polymer solar cells.